Sclerotherapy versus sclerotherapy and propranolol in the prevention of rebleeding from oesophageal varices: a randomised study. Issue 5 (May 1996) - Elsayed, S S; Shiha, G; Hamid, M; Farag, F M; Azzam, F; Awad, M
Abstract : BACKGROUND--This trial was carried out to assess the value of propranolol in the prevention of recurrent variceal bleeding when combined with longterm endoscopic sclerotherapy. PATIENTS AND METHODS--Two hundred patients (161 male, 39 female, age range 20-68 years) with portal hypertension resulting mainly from schistosomal periportal fibrosis or posthepatitic cirrhosis presenting with their first episode of haematemesis or melena, or both were included. This was confirmed endoscopically to result from ruptured oesophageal varices. After initial control of bleeding, patients were randomised into two groups: group 1 treated with endoscopic sclerotherapy alone and group 2 treated with sclerotherapy plus propranolol. They were followed up for two years. RESULTS--Group (2) had a lower rebleeding rate (14.3% v 38.6% in group 1), lower variceal recurrence after obliteration (17% v 34% in group 1), longer period between variceal obliteration and recurrence (36 weeks v 21 weeks in group 1); but no change in mortality (12% in both groups). CONCLUSIONS--Patients treated with sclerotherapy should be given propranolol for longterm management.